Math Problem Statement

Provide a step-by-step solution to the problem in the screenshot; show proof of solution

Let A and B be two matrices. Determine whether the following is true: ((A · B)^T)^(-1) = ((A · B)^(-1))^T.

Solution

To determine whether the given statement

((AB)T)1=((AB)1)T((A \cdot B)^T)^{-1} = ((A \cdot B)^{-1})^T

is true, let's go step by step:


Step 1: Recall Key Matrix Properties

  1. Transposition of a Product: For any matrices AA and BB (of compatible dimensions), we have: (AB)T=BTAT(A \cdot B)^T = B^T \cdot A^T

  2. Inverse of a Product: For invertible matrices AA and BB, we have: (AB)1=B1A1(A \cdot B)^{-1} = B^{-1} \cdot A^{-1}

  3. Inverse of a Transpose: For any invertible matrix MM, we have: (MT)1=(M1)T(M^T)^{-1} = (M^{-1})^T


Step 2: Analyze the Left-Hand Side (LHS)

The LHS is: ((AB)T)1((A \cdot B)^T)^{-1}

Using the property of the transpose of a product: (AB)T=BTAT(A \cdot B)^T = B^T \cdot A^T

Substitute this into the LHS: ((AB)T)1=(BTAT)1((A \cdot B)^T)^{-1} = (B^T \cdot A^T)^{-1}

Now apply the property of the inverse of a product: (BTAT)1=(AT)1(BT)1(B^T \cdot A^T)^{-1} = (A^T)^{-1} \cdot (B^T)^{-1}

Finally, use the property of the inverse of a transpose: (AT)1=(A1)Tand(BT)1=(B1)T(A^T)^{-1} = (A^{-1})^T \quad \text{and} \quad (B^T)^{-1} = (B^{-1})^T

Thus: ((AB)T)1=(A1)T(B1)T((A \cdot B)^T)^{-1} = (A^{-1})^T \cdot (B^{-1})^T


Step 3: Analyze the Right-Hand Side (RHS)

The RHS is: ((AB)1)T((A \cdot B)^{-1})^T

Using the property of the inverse of a product: (AB)1=B1A1(A \cdot B)^{-1} = B^{-1} \cdot A^{-1}

Substitute this into the RHS: ((AB)1)T=(B1A1)T((A \cdot B)^{-1})^T = (B^{-1} \cdot A^{-1})^T

Now apply the property of the transpose of a product: (B1A1)T=(A1)T(B1)T(B^{-1} \cdot A^{-1})^T = (A^{-1})^T \cdot (B^{-1})^T


Step 4: Compare the Two Sides

From Step 2, the LHS is: ((AB)T)1=(A1)T(B1)T((A \cdot B)^T)^{-1} = (A^{-1})^T \cdot (B^{-1})^T

From Step 3, the RHS is: ((AB)1)T=(A1)T(B1)T((A \cdot B)^{-1})^T = (A^{-1})^T \cdot (B^{-1})^T

Thus, the LHS and RHS are equal.


Conclusion

The given statement is true: ((AB)T)1=((AB)1)T((A \cdot B)^T)^{-1} = ((A \cdot B)^{-1})^T


Would you like a more detailed explanation of any step? Here are some questions to explore further:

  1. What are other properties of matrix transposes and inverses?
  2. Can this result be generalized to more than two matrices?
  3. How does this proof work when AA or BB is singular?
  4. Why is the order of multiplication reversed in transposes and inverses?
  5. Can you verify this with numerical examples?

Tip: Understanding matrix properties like these is essential in fields such as linear algebra, computer graphics, and machine learning!

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Matrix Transposition
Matrix Inversion
Linear Algebra

Formulas

Transpose of a product: (A · B)^T = B^T · A^T
Inverse of a product: (A · B)^(-1) = B^(-1) · A^(-1)
Inverse of a transpose: (M^T)^(-1) = (M^(-1))^T

Theorems

Properties of matrix transposition
Properties of matrix inversion

Suitable Grade Level

Undergraduate - Linear Algebra